Pemberdayaan Ekonomi Kreatif melalui Inovasi Pengolahan Limbah Plastik menjadi Eco Paving Block Berbasis Teknologi Tepat Guna - Teardo Said Annajib; Andre Tri Saputra; Afra Duaimatul Insiyah; Shinta Hardiyanti Lukmana (Universitas Muria Kudus, 2026)
The increasing volume of plastic waste poses a serious challenge to environmental management, particularly in communities dominated by household waste. This community service activity aims to empower the community through the innovation of transforming plastic waste into eco paving blocks as an effort to enhance the creative economy. The implementation methods include coordination with partners, socialization, training, material formulation trials, and production assistance. The results show that utilizing 10 kg of plastic waste can produce approximately 25 units of eco paving blocks, with a potential waste reduction of up to 200 kg per month. The resulting products demonstrate good strength and durability, making them feasible for economic development. This program not only contributes to reducing plastic waste but also creates business opportunities for the community through capacity building and the sustainable use of simple technology.